CRISPR/Cas9 and Transgene Verification of Gene Involvement in Unfolded Protein Response and Recombinant Protein Production in Barley Grain - Michael Panting; Inger Baeksted Holme; Jón Már Björnsson; Yingxin Zhong; Henrik Brinch-Pedersen (Frontiers in Plant Science, 2021)
The use of plants as heterologous hosts to produce recombinant proteins has some intriguing advantages. There is, however, the potential of overloading the endoplasmic reticulum (ER) capacity when producing recombinant proteins in the seeds. This leads to an ER-stress condition and accumulating of unfolded proteins. The unfolded protein response (UPR) is activated to alleviate the ER-stress. With the aim to increase the yield of human epidermal growth factor (EGF) and mouse leukemia inhibitory factor (mLIF) in barley, we selected genes reported to have increased expression during ER-induced stress. The selected genes were calreticulin (CRT), protein disulfide isomerase (PDI), isopentenyl diphosphate isomerase (IPI), glutathione-s-transferase (GST), HSP70, HSP26, and HSP16.9. These were knocked out using CRISPR/Cas9 or overexpressed by conventional transgenesis. The generated homozygous barley lines were crossed with barley plants expressing EGF or mLIF and the offspring plants analyzed for EGF and mLIF protein accumulation in the mature grain. All manipulated genes had an impact on the expression of UPR genes when plantlets were subjected to tunicamycin (TN). The PDI knockout plant showed decreased protein body formation, with protein evenly distributed in the cells of the endosperm. The two genes, GST and IPI, were found to have a positive effect on recombinant protein production. mLIF expression was increased in a F2 homozygous GST knockout mutant background as compared to a F2 GST wild-type offspring. The overexpression of IPI in a F1 cross showed a significant increase in EGF expression. We demonstrate that manipulation of UPR related genes can have a positive effect on recombinant protein accumulation.